Development of cognitive behavioral module for out-of-wedlock pregnancy's depression and cognitive distortion - Fauziah Zaiden; Mastura Mahfar (International Journal of Public Health Science (IJPHS), 2023)
Individuals who become pregnant out-of-wedlock require special attention because previous studies have shown that this group is prone to depression and cognitive distortion, which can have an impact on their psychological and life development. Therefore, this article discusses the process of development, validation, and reliability testing of the cognitive behavioral module (modul kognitif tingkah laku/MKT) to manage depression and cognitive distortion of out-of-wedlock pregnant trainees in one of the women’s shelters in Malaysia. This module contains four sub-modules, namely, psychoeducational, behavioral strategies, cognitive strategies and retention of productive behavior that have been developed using the cognitive behavioral therapy (CBT) approach. The validation level assessed by seven expert panels indicated the validity value of the module content was .93. Meanwhile, the reliability test conducted using a questionnaire showed a reliability coefficient of .97. This article demonstrates how a systematic procedure can be used to develop and validate an effective module of depression and cognitive distortion before it can be administered in actual studies. The findings also prove that the MKT module can be applied by counselors or psychological officers to the problems of depression and cognitive distortion experienced by out-of-wedlock pregnant trainees in shelters.